Generation Z and the reality of employment in Indonesia: A problematic portrait of the youngest workforce - Raafi Herdiansyah Putra; Ambar Sari Dewi (Priviet Social Sciences Journal, 2025)
The employment problems experienced by Generation Z (born in 1997-2012) as the youngest workforce are currently attracting the attention of many parties. Various studies and the existing literature show that employment problems are structural and cultural. However, from various studies and literature, there is still not much comprehensive discussion of the various employment problems experienced by this generation. Therefore, this study aims to describe the various employment problems experienced by Gen Z. This research uses a descriptive qualitative approach through library research with Miles and Huberman’s interactive model of data analysis techniques. The results of this study show that there are four main categories that color the dynamics of Gen Z employment: the decline in employment in the formal sector, the generation gap and differences in work preferences, the tendency to be voluntarily unemployed, and the dynamics of the gig economy that color the Gen Z job market. The findings show that Generation Z's employment problems are related to limited employment opportunities and changes in the orientation, values, and expectations of the younger generation towards the world of work, which are interrelated. This research is expected to contribute academically and practically to current employment issues, especially as a study material for developing employment policies that are pro-Gen Z and benefit many parties.